Bibliometric Analysis of Augmented Reality Research Trends in Vocational Education - Fitria Anggraini; Hansi Effendi; Oriza Candra; Titi Sriwahyuni; Doni Tri Putra Yanto (Journal for Lesson and Learning Studies, 2025)
The development of augmented reality (AR) as a digital learning technology offers significant potential to enhance the quality of education, particularly in skills-based learning. However, the utilization of AR in vocational education has not yet been optimally integrated into pedagogical approaches. This study aims to analyze and explore the direction of development, thematic focus, and research dynamics of AR in vocational education through a bibliometric approach. Data were obtained from reputable scientific publications and analyzed using supporting software to identify research trends, academic contributions, dominant fields of study, and relationships among key terms. The results indicate a growing scholarly interest in AR within vocational education alongside advances in digital technology. Existing studies remain largely dominated by technical perspectives, while research addressing the pedagogical integration of AR in vocational learning contexts is still limited. Thematic patterns reveal two main tendencies: the development of AR technologies and applications, and their use in learning processes and learner engagement. In conclusion, this study emphasizes that the advancement of AR in vocational education requires stronger, more contextual, and sustainable pedagogical integration. The findings imply the need for the development of immersive AR-based learning models that are skills-oriented and aligned with the demands of the modern industrial and professional landscape.